Crotaline snake bite in the Ecuadorian Amazon: randomised double blind comparative trial of three South American polyspecific antivenoms - Smalligan, R; Cole, J; Brito, N; Laing, G; Mertz, B; Manock, S; Maudlin, J; Quist, B; Holland, G; Nelson, S; Lalloo, D; Rivadeneira, G; et al. (2004)
Objective: To compare the efficacy and safety of three polyspecific antivenoms for bites from pit vipers. Design: Randomised double blind comparative trial of three antivenoms. Setting: Shell, Pastaza, southeastern Ecuador. Participants: 210 patients with incoagulable blood were recruited from 221 consecutive patients admitted with snake bite between January 1997 and December 2001. Intervention: One of three antivenoms manufactured in Brazil, Colombia, and Ecuador, chosen for their preclinical potency against Ecuadorian venoms. Main outcome measures: Permanent restoration of blood coagulability after 6 and 24 hours. Results: The snakes responsible for the bites were identified in 187 cases: 109 patients (58%) were bitten by Bothrops atrox, 68 (36%) by B bilineatus, and 10 (5%) by B taeniatus, B brazili, or Lachesis muta. Eighty seven patients (41%) received Colombian antivenom, 82 (39%) received Brazilian antivenom, but only 41 (20%) received Ecuadorian antivenom because the supply was exhausted. Two patients died, and 10 developed local necrosis. All antivenoms achieved the primary end point of permanently restoring blood coagulability by 6 or 24 hours after the start of treatment in > 40% of patients. Colombian antivenom, however, was the most effective after initial doses of 20 ml (two vials), < 70 ml, and any initial dose at both 6 and 24 hours. An initial dose of 20 ml of Colombian antivenom permanently restored blood coagulability in 64% (46/72) of patients after 6 hours (P = 0.054 compared with the other two antivenoms) and an initial dose of < 70 ml was effective at 6 hours (65%, P = 0.045) and 24 hours (99%, P = 0.06). Early anaphylactoid reactions were common (53%, 73%, and 19%, respectively, for Brazilian, Colombian, and Ecuadorian antivenoms, P < 0.0001) but only three reactions were severe and none was fatal. Conclusions: All three antivenoms can be recommended for the treatment of snakebites in this region, though the reactogenicity of Brazilian and Colombian antivenoms is a cause for concern.